2020
DOI: 10.5713/ajas.19.0576
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the body surface temperature of sows during the post weaning period and its relation to subsequent reproductive performance

Abstract: Objective: A study was made investigate factors affecting body surface temperature changes after weaning in sows, whether these can be used to aid detection of natural estrus and how they relate to subsequent reproductive performance.Methods: A total of 132 sows were selected during summer from a breeding farm, with mean parity of 3.6±2.3 and 28.5±0.9 days lactation length. Four daily measurements (6:00, 8:00, 16:00, and 18:00) of vulva (VST), udder (UST), ear base and central back skin temperatures for indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In recent years, a large number of methods to accurately predict the onset of oestrus under field conditions have been developed and thus, previous studies have used infrared thermography to detect changes in vulvar skin temperatures, devices to detect changes on electrical resistance of the vaginal mucus and the ultrasonography to detect or predict the occurrence of ovulation (Weng, 2020; Simoes et al, 2014; Hidalgo et al, 2014; Williams & Luzbel de la Sota et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a large number of methods to accurately predict the onset of oestrus under field conditions have been developed and thus, previous studies have used infrared thermography to detect changes in vulvar skin temperatures, devices to detect changes on electrical resistance of the vaginal mucus and the ultrasonography to detect or predict the occurrence of ovulation (Weng, 2020; Simoes et al, 2014; Hidalgo et al, 2014; Williams & Luzbel de la Sota et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual behaviour of the sows during oestrus is affected by oestrogen concentration and is characterized by a variety of signals, such as vocalizations, riding of pen mates when group‐housed, changes in physical activity and/or feed intake decrease (Soede & Kemp, 1997). However, the most important signal is immobilization or ‘standing’ in response to back pressure from a teaser boar, another gilt or sow, or from a person (Soede & Kemp, 1997; Steverink et al, 1999; Simoes et al, 2014; Weng, 2020). Moreover, during oestrus the vulva appears hyperaemic, congested and swollen with a marked increase in its size (Soede & Kemp, 1997; Romoser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the vulvar region of sows has been studied due to the possibility that certain circulatory changes in those animals may indicate of their physiological condition; that is, IRT could help identify the estrus cycle and support assisted reproduction ( 175 ). Some authors suggest that a temperature increase of 2°C in this region can be indicative of estrus, which can be associated with the number of navicular cells ( 176 ). However, no reports have yet determined the sensitivity and specificity that would lead to validating this window in sows.…”
Section: Future Directionsmentioning
confidence: 99%
“…On the other hand, several studies have investigated the relationship between vulvar skin temperature and time of ovulation in swine, concluding that the technique could be an aid in predicting time of ovulation (Luño et al 2013 ; Scolari, 2010). Likewise, Weng ( 2020 ) concluded that infrared thermography could be used for mass screening aimed at the early diagnosis of heat, characterized by an increase of vulvar skin temperature. Still, due to many conflicting parameters as to whether body and/or vaginal temperature is related to the time of oestrus and if those parameters are accurate and reliable, the researchers also state that further studies are needed.…”
Section: Introductionmentioning
confidence: 99%